2018
DOI: 10.3390/ijms19051503
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Human Mesenchymal Stem Cells Derived from Wharton’s Jelly in Spinal Cord Injury Treatment Is Dose-Dependent and Can Be Facilitated by Repeated Application

Abstract: Human mesenchymal stem cells derived from Wharton’s jelly (WJ-MSCs) were used for the treatment of the ischemic-compression model of spinal cord injury in rats. To assess the effectivity of the treatment, different dosages (0.5 or 1.5 million cells) and repeated applications were compared. Cells or saline were applied intrathecally by lumbar puncture for one week only, or in three consecutive weeks after injury. Rats were assessed for locomotor skills (BBB, rotarod, flat beam) for 9 weeks. Spinal cord tissue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 58 publications
4
49
0
Order By: Relevance
“…MSCs can mediate anatomical improvement in the subacute phase after SCI through anti-inflammatory activity, glial scar reduction, and cell bridging effects [50,60]. Our results suggest that MSCs are able to prevent secondary injury by contributing to astroglia suppression, consistent with the results of other studies of MSC transplantation in SCI [61][62][63]. We observed greater reduction of astroglial activation caudally from the injury epicenter after AD-MSCs application compared to other sources of MSCs and the control groups.…”
Section: Discussionsupporting
confidence: 89%
“…MSCs can mediate anatomical improvement in the subacute phase after SCI through anti-inflammatory activity, glial scar reduction, and cell bridging effects [50,60]. Our results suggest that MSCs are able to prevent secondary injury by contributing to astroglia suppression, consistent with the results of other studies of MSC transplantation in SCI [61][62][63]. We observed greater reduction of astroglial activation caudally from the injury epicenter after AD-MSCs application compared to other sources of MSCs and the control groups.…”
Section: Discussionsupporting
confidence: 89%
“…The broad spectrum of pathologies where MSCs can be applied, either as an injectable suspension or within a scaffold or hydrogels, has been reported elsewhere and includes wounds 1,2 , bone and cartilage defects 3 , graft-versus-host disease 4 , cardiovascular 5,6 or neural disorders (multiple sclerosis, stroke, spinal cord injury etc.) [7][8][9] . Previously we have shown that MSC transplantation has a positive impact on neural tissue regeneration in spinal cord injury models 8,10,11 or a protective effect in amyotrophic lateral sclerosis (SOD1G93A) rats 7 .…”
mentioning
confidence: 99%
“…Because WJ-MSCs exert neuroprotective and neurotrophic effects, attempts have been made to also utilize them in spinal cord injury treatment. After the intrathecal transplantation of WJ-MSCs into rats with spinal cord injury, in several studies, the observed effects were similar, namely, an improved locomotor recovery and higher amount of spared gray matter compared to the controls [10,83,84]. Krupa et al [83] tested two dosages of cells (0.5 M and 1.5 M), which were administered one to three times in weekly intervals.…”
Section: Selected Animal Modelsmentioning
confidence: 99%
“…After the intrathecal transplantation of WJ-MSCs into rats with spinal cord injury, in several studies, the observed effects were similar, namely, an improved locomotor recovery and higher amount of spared gray matter compared to the controls [10,83,84]. Krupa et al [83] tested two dosages of cells (0.5 M and 1.5 M), which were administered one to three times in weekly intervals. The results indicated that the effects of treatment are dose-dependent, as 1.5 M of cells provided a better outcome than 0.5 M, and this was enhanced by repeated application [83].…”
Section: Selected Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation